(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Vanderléia Will, an award-winning actress from Santa Catarina, of the Pé de Vento Theater Company, creator of the comic character Dona Bilica and internationally recognized for physical comedy shows De Malas Prontas (2003) and Desajustada(2021), granted an interview to researcher Brígida Miranda. In the conversation held on October 23, 2024, after the presentation of the play Dona Bilica – In Those Days (2014), at CEART/UDESC, the actress revealed dynamics of dramaturgy creation, processes of character development, collection of stories and anecdotes from the old communities of Santa Catarina Island, and reflected on the transformation of her theatrical creation processes following the awakening of feminist consciousness.